Highly engaged but burned out: intra-individual profiles in the US workforce. Issue 1 (6th February 2018) - Moeller, Julia; Ivcevic, Zorana; White, Arielle E.; Menges, Jochen I.; Brackett, Marc A.
Abstract : Purpose: The purpose of this paper is to use the job demands-resources model to investigate intra-individual engagement-burnout profiles, and demands-resources profiles. Design/methodology/approach: A representative sample of the US workforce was surveyed online. Latent profile analysis (LPA) and configural frequency analysis examined intra-individual profiles and their inter-relations. Findings: A negative inter-individual correlation between engagement and burnout suggested that burnout tends to be lower when engagement is high, but intra-individual analyses identified both aligned engagement-burnout profiles (high, moderate, and low on both variables), and discrepant profiles (high engagement – low burnout; high burnout – low engagement). High engagement and burnout co-occurred in 18.8 percent of workers. These workers reported strong mixed (positive and negative) emotions and intended to leave their organization. Another LPA identified three demands-resources profiles: low demands – low resources, but moderate self-efficacy, low workload and bureaucracy demands but moderate information processing demands – high resources, and high demands – high resources. Workers with high engagement – high burnout profiles often reported high demands – high resources profiles. In contrast, workers with high engagement – low burnout profiles often reported profiles of high resources, moderate information processing demands, and low other demands. Originality/value: This study examined the intersection of intra-individual engagement-burnout profiles and demands-resources profiles. Previous studies examined only one of these sides or relied on inter-individual analyses. Interestingly, many employees appear to be optimally engaged while they are burned-out and considering to leave their jobs. Demands and resources facets were distinguished in the LPA, revealing that some demands were associated with resources and engagement.